PREGNANCY RATES AND BODY MORPHOMETRY IN NELLORE COWS SUBMITTED TO PROGESTERONE AND TEMPORARY WEANING OF CALVES - Chacur, M. G. M.; Vasconcelos, F. F.; Dias, H. S.; Aurélio, P. T. F.; Gabriel Filho, L. R. A.; Cremasco, C. P.; Putti, F. F. (Revista Brasileira de Engenharia de Biossistemas, 2015)
Body morphometry and temporary weaning (TW) associated to two protocols of fixed-time artificial insemination (FTAI) with intravaginal progesterone releasing device (IPRD) upon pregnancy rates were evaluated. Cows, at 45-59 days post-partum, were randomly divided into group 1 (n=147) and group 2 (n=197). Group 1: received 1g progesterone (IPRD) and 2mg estradiol benzoate on day 0 (EB-D0); 150mg D-cloprostenol on day 7 (PGF-2a-D7); 0,5mg estradiol cypionate and (TW-48 hours) on day 9 (EC+TW-D9); FTAI on day 11 (D11); group 2: IPRD+EB (D0); PGF-2a+EC+TW (72 hours) on D8; FTAI (D11). The pregnancy rate was higher in cows submitted to TW (72 hours) than in cows with TW (48 hours), or rather, 49.74% vs 30.60% (p<0.05). There was a statistical difference (p<0.05) in groups 1 and 2 between pregnant or non-pregnant cows with regard to body weight (412kg vs 400kg and 419kg vs 390kg) and body condition score (BCS) (3.33 vs 3.08 and 3.53 vs 3/32) respectively. Further, 72-hour weaning associated to the applied protocol improved the pregnancy rate. The evaluation of BCS during post-partum may adjust the start of the breeding season.